2022
DOI: 10.5603/gp.a2021.0182
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal liver function tests in pregnant patients with COVID-19 — a retrospective cohort study in a tertiary center

Abstract: Objectives:The current study aimed to describe the incidence of abnormal liver function tests (LFTs) in pregnant COV-ID-19 patients, explore the association between LFTs with current medication, and provide a reference for medical therapy of pregnant patients with COVID-19. Material and methods:This retrospective single tertiary center cohort study included 122 pregnant patients with confirmed COVID-19 admitted and treated from April 1, 2020, to May 31, 2020. We defined abnormal LFTs as the elevation of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…Similar findings were reported by Deng et al [ 7 ]. Contrary to our findings, Can et al reported significantly low birth weight in pregnant women with COVID-19 complicated by hepatic dysfunction than those without liver dysfunction [ 27 ]. Larger studies are required to further explore the effect of liver dysfunction on neonatal outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported by Deng et al [ 7 ]. Contrary to our findings, Can et al reported significantly low birth weight in pregnant women with COVID-19 complicated by hepatic dysfunction than those without liver dysfunction [ 27 ]. Larger studies are required to further explore the effect of liver dysfunction on neonatal outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, deranged liver function was associated with severe COVID-19 with the extent of derangement being proportional to the severity of COVID-19 [ 29 ]. In their study, Can et al also reported that pregnant women with COVID-19-associated liver dysfunction had an increased frequency of severe disease and longer hospital stay than those without liver dysfunction [ 27 ]. Hence, it can be concluded that pregnancy with COVID-19 complicated by liver dysfunction is associated with a higher risk of disease severity and other maternal complications.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the very rapid spread of the virus, almost the entire population of the country and the world has been infected. In fact, a serious public health emergency has reached the lethal level in communities where healthcare providers are underserved [21]. Therefore, it resulted in serious damages in terms of economic, psychological, education and health by causing restrictions on all continents in mass.…”
Section: Discussionmentioning
confidence: 99%
“…The pregnant women included in the study were classified under the categories asymptomatic, mild, moderate, severe, and critical, in compliance with the guidelines of the National Institutes of Health as per the diagnosis based on physical examinations and vital findings, PCR tests from nasopharyngeal swab samples, chest X-rays, and, if necessary, a thorax computerized tomography (CT). [20,21] Cases that were asymptomatic or classified in the mild disease group (who presented with flu-like symptoms) and the moderate disease group (who had pneumonia, SpO2≥94% in room air, and did not need oxygen therapy) were followed up as outpatients, whereas those in the moderate disease group who required oxygen therapy and those in the severe and critical disease groups were treated as inpatients. During the study period, a total of 501 pregnant women who were COVID-19 positive were hospitalized due to COVID-19 symptoms, obstetric reasons, or both.…”
Section: Methodsmentioning
confidence: 99%